Sosialisasi Sistem Pembayaran Elektronik (QRIS) sebagai Upaya Meminimalisir Penyebaran Covid-19 - Putri, Rosydalina; Wiratama, Pandu; Kurniawan, Agus; Sholihah, Alfiatus; Sari, Yetri Martika (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2021)
The community service program in the form of socialization is carried out in collaboration with the Head of Pekon Karang Sari, Naningan Water District, Tanggamus Regency, Lampung Province. This activity is motivated by the high number of spread of the Covid-19 virus among business actors who are sourced from the circulation of money. This activity was carried out with the aim to provide socialization to the village community about the use of electronic payment system, namely QRIS as an electronic payment tool as one way to avoid covid-19. The method used is to hold socialization door to door to the people who have a business, shop or umkm. The results of this activity increase the understanding of business actors and attract enthusiastic business actors to minimize the use of cash in transactions.